Homogeneous light-induced electron transfer between 9,10-anthracenedione and sodium tetraphenylborate: A channel electrode study - Compton, R; Fisher, A; Wellington, R; Bethell, D (1991)
The electron transfer between excited-state 9,10-anthracenedione (325 nm) and sodium tetraphenylborate (tetraphenylboron sodium) in acetonitrile solution is shown to form the radical anion of 9,10-anthracenedione together with the BPhmath image radical. The latter is known to decompose to biphenyl and other Products. A new channel electrode methodology is developed and characterized to deduce the mechanism of the reaction and to quantify its kinetics.